Pengaruh Sudut Chamfer Terhadap Timing Melt Point Pada Penyambungan Material Mild Steel Menggunakan Las Gesek Rotari - Muhammad Ryan Detra; Yohanes Yohanes; Ridwan Abdurrahman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Rotary friction welding is a type of friction welding which is a type of solid state welding where the welding process is carried out in a solid phase. The friction welding process occurs as a result of the direct conversion of mechanical energy in the form of friction into thermal energy. This research discusses how the effect of the chamfer angle on the timing melt point and the maximum tensile strength in joining mild steel material with the rotary friction welding method, namely by varying the chamfer angle at 0°, 15°, 30°, 45°, 60°. This research uses analytical and experimental methods to analyze the effect of the chamfer angle on the timing melt point. The results of the analysis show that the greater the chamfer angle, then, longer the timing melt point. The lowest average maximum tensile strength value of the joint results was obtained at the variation of the chamfer angle of 0° is 421.17 Mpa and the highest average maximum tensile strength value of the joint results was obtained at the variation of the chamfer angle 45° is 505.53 Mpa. Keywords: Rotary Friction Welding, Chamfer, Timing Melt Point